PELATIHAN PEMANFAATAN PALET BEKAS MENJADI TEMPAT PENYIMPANAN GALON SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT DAN PENGELOLAAN LIMBAH - Agus Sekti Susila Atmojo; Brigida Endah Nuraeni; Edi Sumarya (Jurnal Pengabdian Bukit Pengharapan, 2025)
This community service program was designed to enhance community capacity in transforming discarded wooden pallets into practical and value-added products, specifically gallon storage racks. The program was implemented among residents of Kavling Kamboja RT.001 RW.015, Sungai Pelunggut Village, Sagulung District, Batam City, Riau Islands Province, with the participation of 35 community members. The initiative addressed key issues, including limited utilization of pallet waste and insufficient technical skills to convert such materials into useful and marketable items. The program employed a participatory training approach, integrating theoretical explanation, live demonstrations, and direct hands- on practice. Participants were guided through each stage of production, covering material selection, cutting techniques, assembly processes, and finishing. The outcomes indicate a noticeable improvement in participants’ practical skills and understanding of recycling-based production. Furthermore, the activity contributed to raising environmental awareness and encouraged the development of small-scale economic opportunities through recycled products. Overall, this initiative demonstrates the potential of community-based training as an effective strategy for promoting sustainable waste management and empowering local communities.